Trigonella foenum-graecum L. protects against renal function decline in a mouse model of type 2 diabetic nephropathy by modulating the PI3K-Akt-ERK signaling pathway - Yang Niu; Hongjuan Niu; Luxuan Chi; Peihang Li; Jiyang Du; Xiaoqian Wang; Xu He; Binan Lu; Zongran Pang (Frontiers in Pharmacology)
ObjectivesTrigonella foenum-graecum L. (HLB) exhibits promising pharmacological properties for the treatment of type 2 diabetic nephropathy (DN). This study aims to enhance the understanding of HLB’s pharmacodynamic effects and elucidate the mechanisms underlying its therapeutic potential in DN.MethodsThe pharmacodynamic effects of HLB were initially evaluated in a murine DN model through the oral administration of an aqueous extract of HLB. The primary bioactive constituents were subsequently identified using ultra-high-performance liquid chromatography coupled with high-resolution mass spectrometry (UHPLC-HRMS). Network pharmacology analysis was integrated with these data to uncover potential molecular targets of HLB in DN. Key renal metabolites were profiled using untargeted metabolomics, followed by metabolic pathway enrichment analysis conducted with the MetaboAnalyst 6.0 platform, which facilitated the identification of relevant metabolic pathways through which HLB modulates DN. Finally, quantitative real-time polymerase chain reaction (QRT-PCR) and Western blot (WB) techniques were employed to validate the expression levels of key genes and proteins, thereby confirming the molecular mechanisms underlying the effects of HLB in DN.ResultsAnimal experiments indicated that HLB significantly improved blood glucose regulation and renal function while reducing oxidative stress and abnormalities in lipid metabolism in diabetic mice. A total of 34 compounds and 159 potential therapeutic targets were identified as key active components of HLB. The untargeted metabolomics analysis revealed 61 critical metabolites, among which the PI3K-Akt-ERK signaling pathway—known to be involved in diabetes—was highlighted as a crucial pathway. QRT-PCR and WB analyses demonstrated that HLB upregulated the expression of MAPK1, MAPK3, AKT1, and PI3K.ConclusionThese results suggest that HLB may alleviate DN by modulating oxidative stress and lipid metabolism. Its effects are likely mediated through the PI3K-Akt-ERK signaling pathway, along with the upregulation of MAPK1, MAPK3, AKT1, and PI3K expression. This study lays the groundwork for further investigations into the molecular mechanisms underlying HLB’s action in DN.